Investor protection and International Equity Portfolio Investments - Poshakwale, Sunil S.; Thapa, Chandra (Elsevier Science B.V., Amsterdam., 2011)
The paper examines the influence of investor protection on international equity portfolio investments. Using bilateral portfolio holdings data for 36 countries for 2001-2006, the study demonstrates that the investor protection measures are important determinants of foreign equity portfolio investments. The findings suggest that by improving the quality and enforcement efficiency of legal protections offered to foreign investors, policymakers may be able to attract greater international equity portfolio investments.
Keywords: International equity portfolio investments, Investor protection, Developed and developing countries, Fixed effect models